Detection of Aquifer Infiltration Zones Using Resistivity and Induced Polarization Methods - As'ari As'ari; Seni Herlina J Tongkukut; Ernawatil Gani (Jurnal Ilmiah Sains, 2024)
Infiltration zones that are water providers for aquifers are often neglected, resulting in the sustainable use of groundwater resources will be disrupted. The research is intended to determine rainwater catchment areas as water suppliers for aquifers on the coast of East Tondano Beach. The location of the research is in the coastal area of East Tondano, Minahasa Regency. Exploration of subsurface rock layer detection using the resistivity geoelectric method and induced polarisation, dipole-dipole configuration, 10 m space. Data acquisition using multielectrode resistivity and IP meter MAE type X612-EM. The measurement line of the two methods is the same, the data was measured on 2 lines, with line 1 being 240 m long and line 2 being 360 m long. A rainwater infiltration zone with a resistivity of 48<ρ<192 Ωm was identified, on track 1 there was a infiltration zone at meters 105-135, a layer with low resistivity was identified at meters 70-150 with a resistivity of 3-48 Ωm and a depth of ≥ 15 m.. Based on the results of the IP meter, no suspected groundwater aquifer was found, so rainwater is estimated to flow directly into the sea. On line 2, the infiltration zone was detected at meters 80-105 and meters 275-315. The layer with a low resistivity value at 100-275 meters with a resistivity of 3-48 Ωm, has a depth of ≥ 20 m. The results of the IP measurement, layer with low chargeability ≤ 0.8 ms are found on the 180-200th meter. Suspected groundwater aquifer at 180-200 meters with a depth of 45-65 m. Keywords: Aquifer; resistivity; infiltration zones